Exercise-Induced Fatigue in Hamstring versus Quadriceps Muscles and Consequences on the Torque-Duration Relationship in Men - Massamba, Anasthase; Hucteau, Elyse; Mallard, Joris; Ducrocq, Guillaume P; Favret, Fabrice; Hureau, Thomas J (Medicine and science in sports and exercise, 2022)
The present study investigated the mechanisms of neuromuscular fatigue in quadriceps and hamstring muscles and its consequences on the torque-duration relationship.PURPOSEThe present study investigated the mechanisms of neuromuscular fatigue in quadriceps and hamstring muscles and its consequences on the torque-duration relationship.Twelve healthy men performed a 5-min all-out exercise (3-s contraction, 2-s relaxation) with either quadriceps or hamstring muscles on separate days. Central fatigue and peripheral fatigue were quantified via changes in pre- to postexercise voluntary activation (VA) and potentiated twitch (P Tw ) torque evoked by supramaximal electrical stimulation, respectively. Critical torque was determined as the mean torque of the last six contractions, whereas W ' was calculated as the torque impulse done above critical torque.METHODSTwelve healthy men performed a 5-min all-out exercise (3-s contraction, 2-s relaxation) with either quadriceps or hamstring muscles on separate days. Central fatigue and peripheral fatigue were quantified via changes in pre- to postexercise voluntary activation (VA) and potentiated twitch (P Tw ) torque evoked by supramaximal electrical stimulation, respectively. Critical torque was determined as the mean torque of the last six contractions, whereas W ' was calculated as the torque impulse done above critical torque.After exercise, maximal voluntary contraction (MVC) decreased to a greater magnitude ( P < 0.001) in quadriceps (-67% ± 9%) compared with hamstring (-51% ± 10%). ∆P Tw was also greater in quadriceps compared with hamstring (-69% ± 15% vs 55% ± 10%, P < 0.01), whereas central fatigue only developed in quadriceps (∆VA, -25% ± 28%). Hamstring demonstrated reduced critical torque compared with quadriceps (60 ± 12 vs 97 ± 26 N·m, P < 0.001) as well as drastically lower W ' (1001 ± 696 vs 8111 ± 2073 N·m·s, P < 0.001). No correlation was found between quadriceps and hamstring for any index of neuromuscular fatigue (∆MVC, ∆P Tw , or ∆VA).RESULTSAfter exercise, maximal voluntary contraction (MVC) decreased to a greater magnitude ( P < 0.001) in quadriceps (-67% ± 9%) compared with hamstring (-51% ± 10%). ∆P Tw was also greater in quadriceps compared with hamstring (-69% ± 15% vs 55% ± 10%, P < 0.01), whereas central fatigue only developed in quadriceps (∆VA, -25% ± 28%). Hamstring demonstrated reduced critical torque compared with quadriceps (60 ± 12 vs 97 ± 26 N·m, P < 0.001) as well as drastically lower W ' (1001 ± 696 vs 8111 ± 2073 N·m·s, P < 0.001). No correlation was found between quadriceps and hamstring for any index of neuromuscular fatigue (∆MVC, ∆P Tw , or ∆VA).These findings revealed that hamstring presented different etiology and magnitude of neuromuscular fatigue compared with quadriceps. The absence of correlation observed between quadriceps and hamstring fatigue parameters (∆MVC, ∆P Tw , or ∆VA) suggests no interrelation in fatigue etiology between these two muscle groups within individuals and, therefore, highlights the need to investigate specifically hamstring muscle fatigue.CONCLUSIONSThese findings revealed that hamstring presented different etiology and magnitude of neuromuscular fatigue compared with quadriceps. The absence of correlation observed between quadriceps and hamstring fatigue parameters (∆MVC, ∆P Tw , or ∆VA) suggests no interrelation in fatigue etiology between these two muscle groups within individuals and, therefore, highlights the need to investigate specifically hamstring muscle fatigue.